Identification of Antioxidant Activity by Different Methods of a Freshwater Alga Microspora Sp. Collected From a High Mountain Lake - Zeynep Akar; Bulent Akar; Bulent Sahin (Hittite Journal of Science and Engineering, 2019)
Algae contain a large amount of biological active compounds functioning as antioxidant, antimicrobial and anti-tumour. In the present research, antioxidant activity of freshwater alga Microspora sp. Chlorophyta extract prepared in different solvents methanol, acetonitrile, ethanol, acetone and ethyl acetate was determined with three different methods; 2,2-diphenyl-1-picrylhydrazyl DPPH• , Iron III Reduction / Antioxidant Power FRAP Assay and Copper II Reductive Antioxidant Activity CUPRAC . The alga samples collected from the high mountain lake 2733 m above sea level localized in Gümüşhane province of Turkey. The algal extracts prepared in different solvents showed antioxidant activity. The values of DPPH• varied from 8.97% in acetonitrile extract to 31.15% in methanol extract . As in the DPPH• method, the lowest and highest values in the FRAP method were measured based on μM TEAC Trolox Equivalent Antioxidant Capacity in methanol and acetonitrile extracts as 60.303 μM and 359.394 μM respectively. While the lowest value of CUPRAC test was determined in acetonitrile extract 0.041 μM TEAC as in the other tests, highest value was measured in ethanol extract 0.101 μM TEAC . The values of highest antioxidant activity in both DPPH• and FRAP methods was measured in the methanol solvent whilst was determined in the ethanol solvent for CUPRAC.